Etnoconhecimento do peixe-boi amazônico Trichechus inunguis (Natterer, 1883) pelos pescadores de Novo Airão, Amazonas, Brasil - (:unkn) unknown (Universidade Federal do Amazonas, 2006)
The environmental subjects related to the conservation and protection of the nature plows one of the great world challenges, because they affect the survival of the life about the earth and the relationships between social groups and societies, mainly in the tropical region that possess of the vast diversity of vegetable and animals species, like Amazonian. The appropriation of the resources natural, a lot of times disrespecting social and environmental costs, it can drive the super exploration certain species. From the colonization to the current days, the Amazonian manatee Trichechus inunguis has been hunted for commercial exploitation and subsistence people, that revealing the social and economic importance of the species for the development of the area, through the local cultural influence and of historical facts of the economy that determined the exploration intensity. This aquatic mammal, endemic of the Amazon area, it happens exclusively in fresh water, and set calm, with vegetation abundance alimentary base of this non ruminant herbivore. Besides the commercial exploitation and other factors the species have been classified by the IUCN as vulnerable . In spite of the protection strategies to the species, as creation of protected areas and prohibitive laws of exploration, the consumption and the commercialization of products and by-products are still effective in Amazonian. Thus, some subjects can be lifted up as: importance of the species for the population, local exploitation pressure, hunted strategies, sazonalidade and purpose, and attitudes of conservation of the species for the fishermen. The present study had as main objective to characterize the local knowledge on the Amazonian manatee for the fishermen inhabitants in the New Airão. In this case study, the methodological looked for to understand the processes of interaction of the human populations with the natural resources, based in the theoretical presuppositions of the ethnoecology. Through interviews semi - structured, direct observations; photographic registrations, maps and calendars of social recognition of the fishermen, the collected data were analyzed through cognition tables, in which the information mentioned in the interviews were compared with the information of the scientific literature. Many of these data of the knowledge of the fishermen were validated, giving credit the ethnoecology as cultural product, could subsidize and to complement the academic scientific knowledge. The fishermen have knowledge about the biology and ecology of the Amazonian manatee, describing alimentary habits, reproductive behavior, breathing behavior, and space and temporary notion of use of habitats for the species. The fishing strategies used by the fishermen are traditional, from the technique to the use of handmade equipments, with little introduction of instruments and modern equipments, the amount of fishermen, ally to the behavior of the species, they are factors that favor the survival of the Amazonian manatee population in the area of New Airão. The knowledge acquired by the fishermen integrated into the academic scientific knowledge can subsidize in the formulation of strategies of conservation of the species taking into account the environmental regional aspects of influence in the traditional ecological knowledge and in the patrimonial handling techniques of these fishermen.
Keywords: Etnoconhecimento; Peixe-boi Amazônico; Pescadores; Novo Airão; Rio Negro; Unidades de Conservação; Traditional Ecological Knowledge, Amazonian Manatee; Fishermen; Units of Conservation; CIÊNCIAS AGRÁRIAS